La configuración de ejercicios prácticos en clases de fonética española para alumnos de estudios filológicos (consideraciones metodológicas) - Szałek, Jerzy (Studia Romanica Posnaniensia, 2019)
This study is devoted to methodological considerations on the optimization of practical exercises in Spanish pronunciation classes for modern languages degree students. Combining years of experience with the newest theoretical approaches in the area of articulatory phonetics of the Spanish language, the author presents a host of useful advice and practical arrangements, based on a thorough analysis of phonetic contrast between Spanish and Polish.